(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The main objectives of this study are a study on customer problems of online shopping with special reference to Tirunelveli district. I have selected the sample size 400 respondents in Tirunelveli district. it is used to descriptive research design was selected the present study is confined to analyzing problems in online shopping in the Tirunelveli district, the customers in the district who are engaging in online shopping were defined as the population for this study. The population size could not be measured, so the population size of the study is infinity. Judgmental sampling is adopted for the present study. Online Shopping is a major growth in the field of e-commerce and will certainly be the upcoming buzzword of shopping across the world. In the present era, all online business companies are managing their business online and initiating necessary steps to sell their products or services online.